Interpretation of the Cu K-edge EXAFS spectra of Cu3N using ab initio molecular dynamics. (October 2020) - Bocharov, Dmitry; Anspoks, Andris; Timoshenko, Janis; Kalinko, Aleksandr; Krack, Matthias; Kuzmin, Alexei
Abstract: Cubic copper nitride (Cu3 N) has anti-perovskite structure, and its properties are strongly affected by anisotropic thermal vibrations of copper atoms. Ab initio molecular dynamics (AIMD) simulations were performed in the temperature range from 300 K to 700 K in order to probe the details of Cu3 N lattice dynamics. The Cu K-edge extended X-ray absorption fine structure (EXAFS) spectrum of bulk Cu3 N was used to validate AIMD simulations at 300 K. The AIMD results suggest strong anharmonicity of the Cu–N and Cu–Cu bonds, the rigidity of NCu6 octahedra and strong correlation in atomic motion within –N–Cu–N– atom chains as well as support anisotropy of copper thermal vibrations. Abstract : Highlights: Ab initio molecular dynamics simulations of Cu3 N were performed at 300–700 K. The Cu–N and Cu–Cu bonding is strongly anharmonic. Thermal vibrations of Cu atoms are anisotropic, and NCu6 octahedra are rigid. Strong correlation in atomic motion is present within –N–Cu–N– atom chains.